(untitled) - Taylor, Elizabeth (Penguin Book, 1986)
With a cover design by Celia Birtwell During summer games of hide-and-seek Harriet falls in love with Vesey and his elusive, teasing ways. When he goes to Oxford she cherishes his photograph and waits for the letter that never comes. Then Charles enters her life, and Harriet stifles her imaginings. With a husband and daughter, she excels at respectability: ornaments on the mantlepiece, remembered birthdays and jars of lilac. But when Vesey reappears, her marriage seems to melt away. Harriet is older, it is much too late, but she is still in love with him. First published in 1958, this is Elizabeth Taylor's subtlest and finest work
Keywords: First loves,Man-woman relationships,Marriage,Tình đầu,Quan hệ nam nữ,Hôn nhân